PENGARUH TAMBAHAN PENGHASILAN PEGAWAI (TPP) DAN KEMAMPUAN KERJA TERHADAP KINERJA PEGAWAI PADA BADAN PERENCANAAN, PENELITIAN DAN PEMBANGUNAN DAERAH (BAPPEDA) KABUPATEN MOROWALI - Madjid, Meriana (Katalogis, 2016)
The aims of this research are: 1) to explain and analyze the simultaneous influence of employee income supplement and work capability on employees’ performance in The Agency of Planning, Research, and Regional Development (BAPPEDA), Morowali Regency, positively and significantly; 2) to wxplain and analyze the positive and significant influence of employee income supplement on employees’ performance; 3) to explain and analyze the positive and significant influence of employees’ capability on their performance. The type of this study is causal that is intended to see the influence between variables studied by involving 40 subjects selected through purposive sampling method. Based on multiple linear regression test, this study finds that: 1) employee income supplement and work capability simultaneously have positive and significant influence on employees’ performance in The Agency of Planning, Research, and regional Development (BAPPEDA), Morowali Regency; 2) employee income supplement has positive and significant influence on their performance.